Analisis Konten dan Komparatif Sustainability Report Perbankan Berdasarkan GRI G4 - Rahayu, Norra Isnasia (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
This research is conducted to provide information and compare about the implementation of Sustainability Report applied in each of report. This research is a qualitative research, content analysis is a technique to yield an inference and quantify data to its context. Scoring system is used for mapping the performance of BNI’s and Maybank’s sustainability reporting from its guidelines (context), which is GRI G4. The results of this research shows that both of corporations has implemented good enough Sustainability Report. Despite of the improvement, there are incorrect reporting and ambiguity in some indicators. Corporations still have to make it more complete to achieve all of the performance indicator in the next report. And also their Sustainability Report  towards a better future company.